2005
DOI: 10.1111/j.1440-1681.2005.04264.x
|View full text |Cite
|
Sign up to set email alerts
|

Tocotrienol Offers Better Protection Than Tocopherol From Free Radical‐induced Damage of Rat Bone

Abstract: 1. Free radicals generated by ferric nitrilotriacetate (FeNTA) can activate osteoclastic activity and this is associated with elevation of the bone resorbing cytokines interleukin (IL)-1 and IL-6. In the present study, we investigated the effects of 2 mg/kg FeNTA (2 mg iron/kg) on the levels of serum IL-1 and IL-6 with or without supplementation with a palm oil tocotrienol mixture or alpha-tocopherol acetate in Wistar rats. 2. The FeNTA was found to elevate levels of IL-1 and IL-6. Only the palm oil tocotrieno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
131
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(144 citation statements)
references
References 41 publications
6
131
2
2
Order By: Relevance
“…Both T3 and TP exist in four isoforms, α, β, γ, and δ, and this classification is based on the number and location of the methyl groups on their chromanol rings (http://www.tocotrienol.org). Some evidence has suggested that T3s have greater potential physiologic functions than TPs (7,8). T3 has been shown to mediate its activity against a variety of chronic diseases, including cardiovascular diseases, neurologic diseases, diabetes, and cancer (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Both T3 and TP exist in four isoforms, α, β, γ, and δ, and this classification is based on the number and location of the methyl groups on their chromanol rings (http://www.tocotrienol.org). Some evidence has suggested that T3s have greater potential physiologic functions than TPs (7,8). T3 has been shown to mediate its activity against a variety of chronic diseases, including cardiovascular diseases, neurologic diseases, diabetes, and cancer (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%
“…Few animal studies have examined the effects of alphatocopherol supplementation on bone health but their results are conflicting. Some studies suggest that alpha-tocopherol may improve bone quality and strength, (71,72) maintain BMD, (73) decrease bone resorption, (74) and increase bone formation. (75) Hypothesized mechanisms include preventing the accumulation of bone resorbing cytokines, (76) reducing the number of osteoclasts, (75) and increasing the number of osteoblasts.…”
Section: Discussionmentioning
confidence: 99%
“…mixtures of tocotrienol and tocopherol from palm oil showed better protection against free radical-induced bone damage in rats compared with pure α-tocopherol [1]. Palm oil TRF at the dose of 200 mg/kg also showed a protective effect against many pathological conditions including diabetes-induced atherosclerosis and red blood cells membrane damage [8,26] and oP-induced toxicity in the kidney and pancreas [6,7].…”
Section: Introductionmentioning
confidence: 96%